The encyclopedia of the Spanish-American and Philippine-American wars a political, social, and military history - Tucker, Spencer 1937-; Gale Group (Santa Barbara, Calif. ABC-CLIO, 2009)
Provides a comprehensive overview of the wars that saw the United States emerge as a world power; one that had immense implications for America, especially in Latin America and Asia.
v. 1. A-L -- v. 2. M-Z -- v. 3. Documents.
Electronic reproduction.
Keywords: Spanish-American War, 1898 -- Encyclopedias; Electronic books; Philippines -- History -- Philippine American War, 1899-1902 -- Encyclopedias